Second primary malignancies in cancer survivors: epidemiology, role of anticancer therapy - L. G. Solenova (Успехи молекулярной онкологии, 2016)
The recent years have seen considerable advancement in the therapy of oncology patients and hence better survival and longer lifespan. Thus, studies on the distant effects of antitumor therapy have become increasingly important. That particularly concerns the risk of development of the second primary tumors. The patients that received therapy for the first malignant neoplasm become a higher-risk group for the development of a second tumor for their entire subsequent life. The review represents the data of analytical epidemiological studies on the second leukemia and solid tumors caused by the aftereffects of antitumor therapy using alkylating agents. Data are also considered on the risk of the second tumors that developed upon transplantation of stem cells. The second tumor etiology includes other significant risk factors such as genetic predisposition, smoking, alcohol consumption, imbalanced diet, etc. In combination with the aftereffects of antitumor therapy they may influence significantly the probability of the development of the second tumors in cancer patients, which should be considered in developing preventive measures. The review data suggest the need for cooperation of specialists in various fields and the use of clinical, epidemiological and molecular approaches to study the carcinogenesis of the first and second tumors, the choice of efficient and the safest methods of antitumor therapy to reduce the risk of the development of distant aftereffects and their prevention.